SISTEM INFORMASI PENGELOLAAN ANGGARAN DENGAN METODE R&D - Myra Andriana; Roymon Panjaitan; Tantik Sumarlin (Universitas Bina Sarana Informatika, 2021)
Budget is an important thing in an organization. Budgeting can assist organizations in conducting control and evaluation to achieve goals. The ineffectiveness of a budget will have an impact on the failure of the previously planned activity program. The purpose of this study is to provide a design of a budget management system that can help users to manage their budgets more efficiently and effectively. This study uses research and development methods. The system is built using Visual Basic.Net, with a MySQL database. The result of this research is the creation of an information system that can help in terms of budget management at Sub-Direktorat 2 Ditreskrimum Polda Jawa Tengah. This system makes it easy to input budget data and helps to know the budget amount accurately, because it can reduce the potential for errors. In addition, the presentation of reports can be done quickly so that it can be more efficient.